In the grip of disease - Lloyd, G.E.R. (Oxford University Press, 2003)
This original and lively book uses texts from ancient medicine, epic, lyric, tragedy, historiography, philosophy, and religion to explore the influence of Greek ideas on health and disease on Greek thought. Fundamental issues are deeply implicated: causation and responsibility, purification and pollution, the mind-body relationship and gender differences, authority and the expert, reality and appearances, good government, and good and evil themselves